Ānanda sarbakāje - Sena, Amitā (Ṭegora Risārca Inashṭitiuta, 1983)
Authoress' reminiscences of the life in Visva-Bharati, Santiniketan, and association with the Indian poet Raindranath Tagore, 1861-1941.